The ability of high school students' critical thinking in solving trigonometric problems. (March 2019) - Indrawatiningsih, N; Purwanto; As'ari, A R; Dwiyana; Sudirman; Rahardi, R
Abstract: Critical Thinking has been one of the tools used in our daily life's to deal with the challenges for survival. Developing critical thinking abilities is something which is very important in the world of education today. Problem solving can support increased critical thinking abilities This study aims at describing the students' critical thinking skills in solving Trigonometry problems. Critical thinking ability in this research employs an indicator which consists of Focus, Reason, Inference, Situation, Clarity, and Overview . The type of this research is descriptive research with qualitative approach. The research subjects consist of 3 students, i.e. high-ability student (ST), medium (SS) and low (SR). The results of this study indicate that there are 5 indicators that can be achieved by the high-ability student (ST) namely Focus, Reason, Situation, Clarity, and Overview . Meanwhile the medium students are capable of achieving 2 indicators only, namely Focus and Reason and low ability student achieves 1 indicator of critical thinking ability, namely Reason .